Causes of Drugs Omission among Schizophrenic Patients in Baghdad City - Nabeel M. AL-Dakheely (Indian Journal of Forensic Medicine & Toxicology, 2021)
Drug omission in patients with schizophrenia is the main reason for frequent relapses, poor treatmentoutcome, reduced quality of life and significant increases in healthcare cost.Objectives: This study was conducted to assess the causes of drug omission in patients with schizophreniaand patients at there in Baghdad.Design A descriptive study was carried out in order to achieve the early stated objectives. The study wasinitiated from February 1st, 2017 through May 1st, 2017.Method: Descriptive study one hundred and twenty patients with schizophrenia receiving treatment in IbnRushd mental health hospital and Baghdad teaching hospital were randomly selected to participate in thestudy. Data were collected using a socio-demographic questionnaire, the translated version of the 8-itemMorisky medication adherence scale (MMAS-8). Logistic regression was used to determine significantvariables associated with suboptimal adherence to medication.Results: The prevalence of continuance drug omission by phenomenon schizophrenia patients outgrowand override 51.7%. The factors associated with that were weakness in treatment methods (OR 0.067,95%CI0.012-0.387, P-value 0.03) lack of supervised treatment (OR 0.117, 95%CI 0.038-0.352, P-value<0.001) and also previous experiences about side effects of treatment (OR 4.40, 95%CI= 1.358-14.313p-value 0.01).Conclusions: Medication adherence among patients with schizophrenia is low.Recommendations: The study recommends the need to develop a standard protocol for carrying outadherence counselling to all patients and their relatives